Ectopic Expression of VvSUC27 Induces Stenospermocarpy and Sugar Accumulation in Tomato Fruits - Cai, Yumeng; Yin, Ling; Tu, Wenrui; Deng, Zhefang; Yan, Jing; Dong, Wenjie; Gao, Han; Xu, Jinxu; Zhang, Nan; Wang, Jie; Zhu, Lei; Meng, Qingyong; et al. (Frontiers in Plant Science, 2021)
Seedless fruits are favorable in the market because of their ease of manipulation. Sucrose transporters (SUTs or SUCs) are essential for carbohydrate metabolism in plants. Whether SUTs participate directly in causing stenospermocarpy, thereby increasing fruit quality, remains unclear. Three SUTs, namely VvSUC11, VvSUC12, and VvSUC27 from Vitis vinifera were characterized and ectopic expression in tomatoes. VvSUC11- and VvSUC12-overexpressing lines had similar flower and fruit phenotypes compared with those of the wild type. VvSUC27-overexpressing lines produced longer petals and pistils, an abnormal stigma, much less and shrunken pollen, and firmer seedless fruits. Moreover, produced fruits from all VvSUC-overexpressing lines had a higher soluble solid content and sugar concentration. Transcriptomic analysis revealed more genes associated with carbohydrate metabolism and sugar transport, and showed down-regulation of auxin- and ethylene-related signaling pathways during early fruit development in VvSUC27-overexpressing lines relative to that of the wild type. Our findings demonstrated that stenospermocarpy can be induced by overexpression of VvSUC27 through a consequential reduction in nutrient delivery to pollen at anthesis, with a subsequent downregulation of the genes involved in carbohydrate metabolism and hormone signaling. These commercially desirable results provide a new strategy for bioengineering stenospermocarpy in tomatoes, as well as in other fruit plants.